HUBUNGAN STATUS PEKERJAAN DENGAN PERILAKU IBU DALAM PEMENUHAN GIZI BERDASARKAN KEBIASAAN SARAPAN - Lulut Subekti; Sugeng Mashudi; Metti Verawati (Health Sciences Journal, 2018)
AbstactImproving the quality of human resources (HR) in health and nutrition factors depends on the mother's work, this results in the habits of children requesting extra money for unhealthy breakfasts outside and nutritional disorders in children who experience the process of growth and achievement of children. This study aims to analyze the relationship of employment status to the mother's behavior in the fulfillment of nutrition based on breakfast habits. The design of this research is Correlation with cross sectional approach. Population in this research is all children of class of 2-6 in SDN Mrican 1, District of Jenangan, Regency of Ponorogo with big sample 44 respondents. Sampling of the study using total sampling, data collection using questionnaire and calculation using Chi-Square Test test using SPSS 16.0 error α 0.05. The result of the research on the variables of maternal employment status was interpreted by 28 respondents (63.6%) and 16 respondents (36.4%) did not work. Maternal Behavior variable in nutrient fulfillment interpreted 24 respondents (54.5%) behaved positively and 20 respondents (45.5%) behaved negatively. Chi-Square statistical test obtained p value = 0.001 which means smaller than α = 0.05 Thus it can be said that there is a relationship On the relationship with the relationship niali Contingency Coefficient = 0.447 enough category. Research analysis there is close enough relationship between job status with mother's behavior in nutrition fulfillment based on breakfast habit at SDN Mrican 1, Sub Jenangan, Regency of Ponorogo. Maternal negative behavior in the fulfillment of nutrition that will affect the growth and development of children, the researchers advise on the place of research, especially the school environment put a picture or leaflet about the importance of breakfast for children and breakfast foods. Keywords: work status, behavior, mother, breakfast AbstrakPeningkatkan Kualitas Sumber Daya Manusia (SDM) dalam faktor kesehatan dan gizi tergantung pada pekerjaan ibu, hal ini berakibat pada kebiasaan anak meminta tambahan uang untuk sarapan yang tidak sehat diluar dan gangguan nutrisi pada anak yang mengalami proses tumbuh kembang dan prestasi anak. Penelitian ini bertujuan untuk menganalisis hubungan status pekerjaan dengan perilaku ibu dalam pemenuhan gizi berdasarkan kebiasaan sarapan.Desain penelitian ini adalah Korelasi dengan pendekatan cross sectional. Populasi pada penelitian ini adalah seluruh anak kelas 2-6 di SDN Mrican 1, Kecamatan Jenangan, Kabupaten Ponorogo dengan besar sampel 44 responden. Sampling penelitian menggunakan Total sampling, pengumpulan data menggunakan kuesioner dan perhitungan menggunakan uji Uji Chi-Square menggunakan SPSS 16.0 kesalahan α 0,05.Hasil penelitian menunjukkan Status pekerjaan ibu diinterpretasikan 28 responden (63,6%) bekerja dan 16 responden (36,4%) tidak bekerja. Variabel Perilaku ibu dalam pemenuhan gizi diinterpretasikan 24 responden (54.5%) berperilaku positif dan 20 responden (45,5%) berperilaku negatif. uji statistik Chi-Square diperoleh nilai Contingency Coefficient =0,447, dan p value = 0,001 yang berarti lebih kecil dari α= 0,05 berarti ada hubungan cukup antara status pekerjaan dengan perilaku ibu dalam pemenuhan gizi berdasarkan kebiasaan sarapan.Perilaku negatif ibu dalam pemenuhan gizi sehingga akan mempengaruhi tumbuh kembang anak, maka peneliti menyarankan pada tempat penelitian terutama lingkungan sekolah memasang gambar atau leaflet tentang pentingnya sarapa n pagi bagi anak dan jenis makanan sarapan pagi.Kata kunci: status pekerjaan, perilaku, ibu, sarapan.